THE EFFECT OF GIVING DRAGON FRUIT (Hylocereus polyrhizus) PEEL JUICE THROUGH DRINKING WATER ON THE INTERNAL ORGANS OF MALE BALI DUCKS - N.L.P.A., Agustini,; Candrawati, D. P. M. A.; Wirapartha, M. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
Since there is a ban on the use of Antibiotic Growth Promoter (AGP) in livestock because it is suspected that the use of this antibiotic can produce residues that settle in the livestock's body, an alternative natural feed additive is needed, in the form of dragon fruit peel. This study was targeted to observe the impact of distributing dragon fruit peel juice from drinking water in the internal organs of ducks and was carried out in Gulingan Village, Badung Regency, Mengwi District, for 8 weeks. This study used RAL/Completely Randomized Design including 4 actions and 5 replications so there were 20 trial units and each replication included 3 male Bali ducks. The actions distributed were in the form of ducks being given drinking water without juice (P0), for ducks being given 6% juice from drinking water (P1), ducks being given 8% juice from drinking water (P2), and ducks being given 10% juice from drinking water (P3). This study looked at variables that included the percentage of liver, heart, pancreas, bile, small intestine, spleen, and length of the small intestine. The results of the study showed that the distribution of dragon fruit peel juice at levels of 6%, 8% and 10% had no significant impact (P>0.05) on the percentage of bile, liver, small intestine, spleen and length of the small intestine. However, the distribution of juice at 6% of drinking water significantly (P<0.05) increased the percentage of the heart and also minimized the percentage of the pancreas. The conclusion is that adding dragon fruit peel juice to 10% of drinking water does not have a negative impact on the organs of male Bali ducks.